2013
DOI: 10.1093/pasj/65.sp1.s10
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Negative Bursts as Indications of Reconnection Between Eruptive Filaments and a Large-Scale Coronal Magnetic Environment

Abstract: Low-temperature plasma ejected in solar eruptions can screen active regions as well as quiet solar areas. Absorption phenomena can be observed in microwaves as “negative bursts” and in various spectral domains. We analyze two very different recent events with such phenomena, and present an updated systematic view of solar events associated with negative bursts. Related filament eruptions can be normal, without essential changes of shape and magnetic configuration, and “anomalous.” The latter are characterized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 18 publications
1
20
0
3
Order By: Relevance
“…The center of the flux rope has shifted across B, while plasma (gray) has departed from the flux rope and moves along the outer field B. The scheme in Figure 13 is basically similar to Figure 6 in Grechnev et al (2013). The apparent difference between the schemes is due to different directions of motions of the eruptive filaments through the magnetic null point in the quadrupolar magnetic configuration.…”
Section: Trajectory and Mass Depletion Of The Eruptive Filamentmentioning
confidence: 72%
See 1 more Smart Citation
“…The center of the flux rope has shifted across B, while plasma (gray) has departed from the flux rope and moves along the outer field B. The scheme in Figure 13 is basically similar to Figure 6 in Grechnev et al (2013). The apparent difference between the schemes is due to different directions of motions of the eruptive filaments through the magnetic null point in the quadrupolar magnetic configuration.…”
Section: Trajectory and Mass Depletion Of The Eruptive Filamentmentioning
confidence: 72%
“…The complex reconnection of a flux rope with the adjacent field in complex magnetic topology has been also described by, e.g., Lugaz et al (2011), Zuccarello et al (2012), and Masson, Antiochos, and DeVore (2013). Grechnev et al (2008Grechnev et al ( , 2011aGrechnev et al ( , 2013 have found observational evidence of magnetic reconnection between the internal field belonging to the eruptive filament and the preexisting coronal field. This is a phenomenon of plasma dispersal from an eruptive filament over the solar surface that is visible as the disintegration of the filament.…”
Section: Introductionmentioning
confidence: 75%
“…As a result, both open and closed structures of these domains become filled with energetic particles as well as cool plasma of the pre-eruptive filament. Related schemes containing a single null point were discussed by Gary and Moore (2004), Masson, Antiochos, and DeVore (2013), Meshalkina et al (2009), Grechnev et al (2013b), and Uralov et al (2014. Stretching a large-scale quadrupole into the solar wind might cause disappearance of the null point.…”
Section: Appearance Of Accelerated Particles In a Trapmentioning
confidence: 99%
“…As noted in Section 3, multi-frequency observations of microwave depressions provide the basis for plasma diagnostics in erupting structures. Modeling the spectrum of the absorption depths observed at a few frequencies from 1 to 10 GHz allowed estimating parameters of the erupted material responsible for several negative bursts even without images (Grechnev et al, 2008(Grechnev et al, , 2013bKuzmenko et al, 2009;Kuzmenko and Grechnev, 2017). These studies used a flatlayered model of a relatively large absorbing cloud of given height, dimensions, temperature, and density, with a possible stable compact microwave source covered.…”
Section: Summary On the Eruptions Observed With The Srhmentioning
confidence: 99%